Comparative assessment of severity and prognosis of acute pancreatitis through APACHE II and HAPS predictor models - Alam, Maboob; Agrawal, Priyanka; Singh, Rohit K.; Singh, Krishna K.; Pratap, Dhirendra (International Journal of Research in Medical Sciences, 2021)
Background: Acute pancreatitis is one of the leading causes of hospitalization amongst all gastrointestinal disorders with high burden of morbidity and mortality. Predicting the progression of AP in terms of course and outcome to determine suitable management strategy and level of care is challenging. A number of predictor models are developed to predict the severity of acute pancreatitis but they vary in their definitions of severity. HAPS have been proposed as a simple scoring tool for assessment of severity and prognosis of acute pancreatitis. Thus, the aim of present study was to investigate the usefulness of HAPS predictor model against APACHE II model. Methods: Current investigation was a hospital based prospective study conducted on 80 proven cases of acute pancreatitis at K. K. hospital, Uttar Pradesh. The serum amylase and lipase levels of all enrolled patients, were tested and measured at admission, and at 48 and 72 hours post admission. The pancreatitis-specific clinical investigations like; HAPS, APACHE II were calculated and assessed statistically in terms of sensitivity, specificity, positive and negative predictive values and accuracy. Results: The findings of present investigation revealed that amongst the two scoring systems, APACHE II was superior predictor model in terms of sensitivity and specificity for various outcomes like severe acute pancreatitis, hospital stay >7 days and in-hospital mortality. However, HAPS exhibited high specificity for all the outcomes. Conclusions: HAPS can be recommended as a useful tool for early evaluation of acute pancreatitis in patients specifically in primary care settings of developing countries like India.